2003
DOI: 10.4067/s0717-71782003000100002
|View full text |Cite
|
Sign up to set email alerts
|

Early life stages of development of the red porgy Pagrus pagrus (Pisces, Sparidae) in captivity, Argentina

Abstract: ABSTRACT. The early life history, from egg to juvenile, of red porgy Pagrus pagrus, in captivity is described. Yolk larvae were hatched 50 hours after fertilization, at 18°C water temperature. The opening of the mouth took place between the third and fourth day after hatching, corresponding to 2.6-2.8 mm notochordal length. The transformation stage began at 9 mm standard length, approximately 40 days after hatching. The appearance of the fins favored the displacement of pelagic larvae towards the bottom, acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
3
8
1
2
Order By: Relevance
“…Values of OD and OdD were coincident with those previously reported for both wild and captive red porgy (Machinandiarena et al, 2003;Radonic et al, 2005). Our results suggest that hydrated oocytes sampled in 2010 had a greater amount of reserves, suggesting an egg quality higher than in other years analyzed.…”
Section: Discussionsupporting
confidence: 75%
“…Values of OD and OdD were coincident with those previously reported for both wild and captive red porgy (Machinandiarena et al, 2003;Radonic et al, 2005). Our results suggest that hydrated oocytes sampled in 2010 had a greater amount of reserves, suggesting an egg quality higher than in other years analyzed.…”
Section: Discussionsupporting
confidence: 75%
“…This requires a fast development of different structures and tissues related to prey capture and digestion (Roo et al, 1999). Complete yolk exhaustion was observed between three to four DAH at 18°C of rearing temperature, in coincidence with previous studies made by Machinandiarena et al (2003), Aristizábal & Suárez (2006) and Aristizábal et al (2009). Starved larvae survived up to nine DAH, when a mass mortality was observed.…”
Section: Discussionsupporting
confidence: 65%
“…Morphological development of red porgy larvae was described by Machinandiarena et al (2003). They found that mouth opening takes place between three and four DAH in coincidence with the exhaustion of yolk reserves using the same methodologies and rearing protocol herein employed.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, notochord flexion of P. pagrusappeared at 5.56±0.43 mm TL. In contrast, it was reported that the beginning of the notochord flexion of P. pagrus occurred at 4.40 mm standard length (Machinandiarena et al 2003). In addition to this, notochord flexion was observed at 5.4 mm TL in Pagellus erythrinus (Sfakianakis et al 2004), 6.5 mm TL and 7.1 mm TL in S. aurata (Çoban et al, 2008b;Koumoundouros et al 1997), 5.6 mm TL in P. pagrus (Çoban et al 2008a) and 6.4 mm TL in D. sargus larvae (Koumoundouros et al 2001).…”
Section: Discussionmentioning
confidence: 86%
“…In the last decade, numerous studies have been carried out on red porgy reproduction and physiology (Kokokiris et al 1999;Hood and Johnson 2000), larval rearing (Hernandez-Cruz et al 1999;Roo et al, 1999;Machinandiarena et al 2003), feeding (Papandroulakis et al 2004), osteological development (Çoban et al, 2009a) and digestive enzyme activities (Darias et al 2006;Suzer et al 2007). In contrast, literature regarding the early life history of larval red porgy reared in intensive culture conditions is scarce, either fragmentary or related to the internal morphology of a few individuals caught in the wild (Alarcon and Alvarez, 1999), morphological and histological features (Diaz et al, 2013) and/or limited to yolk-sac larvae and larval development under captivity (Mihelakakis et al 2001).…”
Section: Introductionmentioning
confidence: 99%